Revolutionizing Rice Grain Quality: A Holistic Review Integrating Conventional and Molecular Approaches - Sadhu, Supratim; Kole, Paresh Chandra (International Journal of Bio-resource and Stress Management, 2024)
This review mainly focuses on the rice grain quality based on which rice varieties are distinguished into several quality classes like, physical quality, eating and cooking quality and nutritional quality. The rice breeding programme needs to focus on the development of nutrient-dense rice for value addition, helping in reducing malnutrition and Vitamin-A deficiency (VAD). There is enough scope to enhance the nutritional and cooking quality in small and medium grain rice germplasm by bringing them into the breeding programme through Fe and Zn and Vitamin-A biofortification, aided with molecular techniques. Many studies have been conducted to find out the quantitative trait locus (QTL) for enhancing the quality of grain. The QTL qBRR5 and qBRR3 are responsible for brown rice grain width and length found on chromosome 5 and on chromosome number 3, respectively and for head rice on chromosome number 1, 5, and 6. The QTLs present on chromosomes 3, 5, and 6 are responsible for head rice recovery, chalky appearance of rice grain as well as grain size and shape. The gene Wx, located on chromosome 6 linked with the QTL qAC6 regulate amylose content and gel consistency. The QTL SSIIa on chromosome 6, control both the amylopectin and gelatinization temperature. The QTLs for Fe and Zn content in rice grain are located on chromosome 2, 3, 8, 11 and 12. Development of “Golden rice” and innovations with Arabidopsis genes can significantly enhance β-carotene levels and address Vitamin-A deficiency, while RNAi techniques improve storage quality.